2008
DOI: 10.1093/cercor/bhn075
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prefrontal Cortex CB1 Receptors in the Modulation of Fear Memory

Abstract: Understanding the mechanism of how fear memory can be extinguished could provide potential therapeutic strategies for the treatment of posttraumatic stress disorders. Here we show that infusion of CB1 receptor antagonist into the infralimbic (IL) subregion of the medial prefrontal cortex (mPFC) retarded cue-alone-induced reduction of fear-potentiated startle. Conversely, cannabinoid agonist WIN55212-2 (WIN) facilitated the extinction. Unexpectedly, administration of WIN without cue-alone trials reduced startle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
86
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 46 publications
10
86
2
3
Order By: Relevance
“…On the other hand, CB1 agonists mimicked extinction training, facilitating and causing a reduction of startle potentiation in a dose-dependent manner. The effect of CB1 agonists was mimicked by the endocannabinoid uptake inhibitor AM404 and the fatty acid amidehydrolase inhibitor URB597, and could be blocked by a specific CB1 receptor antagonist (Lin et al 2008). In the present study, we show that WIN-pretreated rats exhibited much less extinction to cue-alone presentations.…”
Section: Discussionsupporting
confidence: 55%
“…On the other hand, CB1 agonists mimicked extinction training, facilitating and causing a reduction of startle potentiation in a dose-dependent manner. The effect of CB1 agonists was mimicked by the endocannabinoid uptake inhibitor AM404 and the fatty acid amidehydrolase inhibitor URB597, and could be blocked by a specific CB1 receptor antagonist (Lin et al 2008). In the present study, we show that WIN-pretreated rats exhibited much less extinction to cue-alone presentations.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies reported an increase in Fos-ir in the central amygdala of naive mice following pharmacological blockade of CB1 (Patel et al, 2005a). In addition, CB1 plays a complex role in the regulation of fear and anxiety within the medial prefrontal cortex (Lin et al, 2009), and neuronal activity within the prelimbic cortex seems to directly Figure 6. Neuroanatomical signature of extinction training.…”
Section: Discussionmentioning
confidence: 98%
“…Recent evidence, however, suggests that activity in the medial prefrontal cortex (mPFC) is critical for cued fear learning, in addition to the amygdala (Quirk et al, 1995(Quirk et al, , 2003. As anatomical evidence demonstrates that CCK, CCKBR and Cnr1 localize to prefrontal cortex (Larsson and Rehfeld, 1979;Zarbin et al, 1983;Herkenham et al, 1990) and behavioral studies implicate prefrontal Cnr1 in fear (Laviolette and Grace, 2006;Lin et al, 2008Lin et al, , 2009Ganon-Elazar and Akirav, 2013;Kuhnert et al, 2013), similar immunofluorescence experiments should be performed in mPFC. In addition, site-specific behavioral experiments should be conducted in follow-up studies to determine whether the observed Cnr1-CCKBR interaction occurs in BLA.…”
Section: Discussionmentioning
confidence: 99%